Design and characterization of spice fused tamarind starch edible packaging films. (May 2016) - Chandra mohan, C.; Rakhavan, K.R.; Sudharsan, K.; Radha krishnan, K.; Babuskin, S.; Sukumar, M.
Abstract: The main aim of this study was to produce and optimize spice fused tamarind seed starch edible films for meat packaging. Among fourteen different spices examined for incorporation with tamarind starch edible films, ball milled Syzygiumaromaticum and Cinnamomum cassia were selected because of its high preservative properties. Ball milled spices were found to have break point for release of active compounds. Break point sample of S. aromaticum was found to have high antioxidant property with total phenolic content of 29.31 ± 0.31 mg GAE/g. Break point sample of C. cassia was found to have high antibacterial activity against a panel of food pathogenic and meat putrefying bacteria. Edible films prepared from tamarind seed starch were studied for its mechanical properties. Artificial Neural Network (ANN) model was developed for prediction of mechanical properties of edible film using central composite design experimental data. Examined model of Probabilistic neural network was found to be fit for experimental data with average correlation coefficient (R 2 ) of 0.989. Minimum inhibitory concentration mixture of S. aromaticum and C. cassia was supplemented with optimized edible film mixture and improvement in antioxidant and antibacterial properties of edible films were observed. Graphical abstract: Highlights: Edible film packages were produced from amylose rich tamarind seed starch. PNN model found to be an interesting tool for optimization of edible film. Particle size reduction was found to be an alternative method to embrace spice properties. Spice fused edible films were found to be a potential food preservative package.